Subcutaneous Trastuzumab: An Observational Study of Safety and Tolerability in Patients with Early HER2-Positive Breast Cancer - Otoya, I (2024)
Purpose: In Peru, breast cancer (BC) stands as the most predominant malignancy neoplasm among women. Trastuzumab has marked a significant milestone in the management of this disease. It has been shown to improve prognosis in human epidermal growth factor receptor 2 (HER2)-expressing female patients, but its repercussions and efficacy are yet to be analyzed in a context with limited resources. Methods: The study population is made of woman patients aged 18 years and older diagnosed with HER2-positive BC at Instituto Nacional de Enfermedades Neoplásicas (INEN, Lima, Peru) during 2019-2021 and treated with at least one dose of subcutaneous trastuzumab. We reviewed medical records to register treatment characteristics, adverse events (AEs), disease progression, and survival status. We considered a median follow-up time of 36 and 45 months for progression and survival status. Results: The majority of patients were over 50 years old (54.29%). Tumor size averaged 19.7±16.1 mm. Lymph nodes were present in 44.78% of patients. Most patients received adjuvant chemotherapy (63.8%) as first-line treatment. Descriptive analyses of treatment outcomes revealed a 30% toxicity rate, primarily attributed to arthralgia (47.62%), followed by diarrhea, fatigue, and injection site reactions, with relatively lower discontinuation rates compared to larger scale studies. Differences in demographic, clinical, and treatment characteristics were not statistically significant concerning the emergence of AEs (p>0.05). Progression appeared in nine patients, and the overall survival (OS) rate stood at 98.6% and 92.8%, respectively, during a median follow-up of 36 and 45 months. Conclusion: The research suggests that subcutaneous trastuzumab is comparable in effectiveness and safety to the intravenous administration. Regional-specific studies may provide valuable insights into demographic factors influencing treatment outcomes in Peru or other countries. Furthermore, it could represent a more accessible alternative, potentially enhancing patient adherence and optimizing healthcare resource logistics. © 2024 Iris Otoya et al.